A quantitative and predictive model for RNA binding by human Pumilio proteins - Jarmoskaite, Inga; Denny, Sarah K; Vaidyanathan, Pavanapuresan P; Becker, Winston R; Johan Ol Andreasson; Layton, Curtis J; Kappel, Kalli; Shivashankar, Varun; Sreenivasan, Raashi; Das, Rhiju; Greenleaf, William J; Herschlag, Daniel (bioRxiv, 2018)
High-throughput methodologies have enabled routine generation of RNA target sets and sequence motifs for RNA-binding proteins (RBPs). Nevertheless, quantitative approaches are needed to capture the landscape of RNA/RBP interactions responsible for cellular regulation. We have used the RNA-MaP platform to directly measure equilibrium binding for thousands of designed RNAs and to construct a predictive model for RNA recognition by the human Pumilio proteins PUM1 and PUM2. Despite prior findings of linear sequence motifs, our measurements revealed widespread residue flipping and instances of positional coupling. Application of our thermodynamic model to published in vivo crosslinking data reveals quantitative agreement between predicted affinities and in vivo occupancies. Our analyses suggest a thermodynamically driven, continuous Pumilio binding landscape that is negligibly affected by RNA structure or kinetic factors, such as displacement by ribosomes. This work provides a quantitative foundation for dissecting the cellular behavior of RBPs and cellular features that impact their occupancies.